A Paradigm Shift: Outcomes of Early Autologous Breast Reconstruction after Radiation Therapy - Elver, Ashlie A.; Egan, Katie G.; Cullom, Melissa E.; Nazir, Niaman; Johnson, Braden M.; Limpiado, MarcArthur; Holding, Julie; Lai, Eric C.; Butterworth, James A. (Journal of Reconstructive Microsurgery, 2022)
Background Radiation creates significant challenges for breast reconstruction. There is no consensus regarding optimal timing for autologous reconstruction following radiation. This study explores clearly defined, shorter time intervals between completion of radiation and reconstruction than previously reported.Methods A retrospective review was performed on patients who underwent autologous reconstruction by five microsurgeons at an academic institution from 2009 to 2020. Cohorts were selected by time elapsed between radiation and autologous reconstruction including <3 months, 3 to 6 months, 6 to 9 months, 9 to 12 months, 12 to 24 months, and >24 months. Analysis compared baseline characteristics, operative details, complications, revision rates, and BREAST-Q scores. Analysis of variance was used for continuous variables and chi-square for discrete variables.Results In total, 462 radiated patients underwent 717 flaps. There were 69 patients at <3 months (14.9%), 97 at 3 to 6 months (21%), 64 at 6 to 9 months (13.9%), 36 at 9 to 12 months (7.8%), 73 at 12 to 24 months (15.8%), and 123 at >24 months (26.6%). Age, time from mastectomy, and failure of primary reconstruction were higher at >24 months (p < 0.001). There was no difference between cohorts in intraoperative complications in radiated or nonradiated breasts. There was no difference in acute and late postoperative complications between cohorts. Wound-healing complications in radiated sides were lowest at <3 months and 3 to 6 months (5/69 [7.3%] and 11/97 [11.3%], respectively) compared with other groups (18.8–22.2%) but did not reach significance (p = 0.11). More fat graft revisions occurred at <3 months (p = 0.003).Conclusion Reconstruction can be safely performed within 3 months after radiation without increases in intraoperative, acute, or late reconstructive complications.
Keywords: radiation; autologous reconstruction; breast reconstruction